The Strategy and Competitive Advantage of Indoor Sports Industry in Malaysia - Tan, Kar Fai (2011)
The sports industry in Malaysia is an industry which is full of potential as it is considered young in this country. The most popular sports in Malaysia are football (soccer) and badminton. Other sports such as squash, cycling, hockey are also quite popular due to our national representative success in the international arena. The purpose of this study is to determine the strategy taken by firms operating in indoor sports industry in Malaysia and to know their competitive advantage. The methodology used here is qualitative research face to face interview studies where primary data is collected through this method with sports venue operators in Klang Valley. The result of the research shown that the strategy taken supports the competitive advantage of the sports firm operating in Klang Valley.